2017
DOI: 10.3390/sports5020038
|View full text |Cite
|
Sign up to set email alerts
|

What is Trained Develops! Theoretical Perspective on Skill Learning

Abstract: Knowledge about developmental theories is important for experts or specialists working with children following normal development and children who have various kinds of dysfunction, in order to better understand what happens with processes associated with motor behavior. In this article, we have explored how theories of development and learning can be used to understand processes associated with motor behavior. A probabilistic perspective emphasizes that the changes taking place in the development is a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
2
28
0
1
Order By: Relevance
“…In other words, the changes that reading makes to our brain results from the effect of our experience with reading. These findings can be used as an argument for the task specificity principles of learning across cognitive and motor skills, as the processes associated with learning may seem relatively independent and specific ( Kleim and Jones, 2008 ; Sigmundsson et al, 2013 , 2017 ; Stöckel and Hughes, 2015 ). Gender differences in reading is both growing and consistent ( Stoet and Geary, 2013 ) yet it is ignored in the literature ( Dodd and Carr, 2003 ).…”
Section: Discussionmentioning
confidence: 92%
“…In other words, the changes that reading makes to our brain results from the effect of our experience with reading. These findings can be used as an argument for the task specificity principles of learning across cognitive and motor skills, as the processes associated with learning may seem relatively independent and specific ( Kleim and Jones, 2008 ; Sigmundsson et al, 2013 , 2017 ; Stöckel and Hughes, 2015 ). Gender differences in reading is both growing and consistent ( Stoet and Geary, 2013 ) yet it is ignored in the literature ( Dodd and Carr, 2003 ).…”
Section: Discussionmentioning
confidence: 92%
“…Low levels of motor competence have been reported for both children and adolescents in many countries [8][9][10][11]. In order to increase these levels among children and youth who are potentially missing out on developing motor behaviors that are important for normal growth and development, practice and instruction are needed to facilitate motor development [12]. Indeed, research has consistently demonstrated that scheduled programs that are developmentally and age appropriate (for children or adolescents), activity-based, task-specific, and/or have a high level of autonomy are efficient interventional methods for improving various aspects of motor competence [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Possessing certain motor skills allows the child to participate in varied physical activities, which in turn facilitates versatile movement experiences [10]. At the same time, stimuli and experience through participation in physical activity give rise to both quantitative and qualitative changes in motor development, that is, learning new motor skills and increasing the quality of movement in skills already learned [11,12]. In recent years, a decline in motor skills in children and adolescents has been reported [13][14][15].…”
Section: Introductionmentioning
confidence: 99%